1994
DOI: 10.3109/00365529409094893
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Effects of Intraduodenal Tryptophan on Pyloric and Duodenal Motility in Humans

Abstract: We conclude that intraduodenal tryptophan has stereospecific effects on pyloric and duodenal motility. Although the precise contribution of these differential effects to gastric emptying remains to be clarified, they may be partially responsible for the differences in gastric emptying of D-tryptophan and L-tryptophan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Reduced antral motility may explain the delay in gastric emptying seen during infusion of intravenous amino acids 14. A recent study showed that intraduodenal l -tryptophan stimulates pyloric motility and may induce premature duodenal phase III activity 20. The present study shows that not only intraluminal but also intravenous amino acids affect antroduodenal motility.…”
Section: Discussionsupporting
confidence: 53%
“…Reduced antral motility may explain the delay in gastric emptying seen during infusion of intravenous amino acids 14. A recent study showed that intraduodenal l -tryptophan stimulates pyloric motility and may induce premature duodenal phase III activity 20. The present study shows that not only intraluminal but also intravenous amino acids affect antroduodenal motility.…”
Section: Discussionsupporting
confidence: 53%
“…Interdigestive phases were recognized visually according to established criteria (17). The manometric recordings obtained after completion of the intraduodenal nutrient infusion were analyzed in 10-min blocks.…”
Section: Manometric Analysismentioning
confidence: 99%
“…11 In health, nutrient delivery from the stomach to the small intestine is tightly regulated at 2-3 kcal/min 12 by small intestinal feedback. Small intestinal glucose 13 , lipid, 14 and amino acid 15 infusions stimulate pyloric and suppress antral and duodenal motility. The increase in pyloric motility is associated with slowing of gastric emptying 16 as a consequence of occlusion of transpyloric flow.…”
mentioning
confidence: 99%